Gambaran Kualitas Hidup Saudara Kandung Penyandang Autism Spectrum Disorder (Penelitian pada Remaja Akhir di Jakarta) - Pricilia Claudia Pattynama; Weny Savitry S. Pandia (Jurnal Perkotaan, 2016)
Autism Spectrum Disorder (ASD) in families affect sibling’s quality of life. Quality of life is an individual's perception of life in cultural contexts and values in the environment. It consists of subjective and objective domain. This study used a qualitative approach. Interviews with two subjects were implemented. The results showed that siblings generally have a good quality of life; but not in dimensions of joint activity and environmental acceptance. Factors affecting the quality of life is parenting practises, disability level, the values, and economic status.